Teacher Professionalism as the Central Educational Figure in Shaping Students’ Islamic Character at MTs Zia Salsabila - Ayuningtyas, Nanda; Ritonga, Asnil Aidah (FKIP - Universitas Riau, 2025)
This study explores the meaning of teacher professionalism as the central figure in shaping students’ Islamic character at MTs Zia Salsabila, drawing on Imam Al-Ghazali’s theoretical framework which emphasizes instruction, role modeling, and guidance as core elements of moral education. Using a qualitative phenomenological approach, data were gathered through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model involving data collection, reduction, presentation, and conclusion verification. The findings reveal that teachers perceive professionalism as a moral trust to nurture an Islamic generation, embodied in four core competencies pedagogical, personal, social, and professional with personal competence emerging as the most influential in developing students’ Islamic character, particularly through consistent role modeling, empathy, and adherence to Islamic values. The novelty of this research lies in highlighting teachers not merely as educators but as pivotal moral exemplars, while offering a unique perspective by focusing on MTs Zia Salsabila, an institution rarely examined in previous studies, thus enriching the discourse on implementing Islamic character education through teacher role modeling.